Use Of Augmented Reality as an Alternative Media for Learning Mathematics: A Systematic Literature Review - Dina Prasetyowati; Wardono Wardono; Scolastika Mariani; Nuriana Rachmani Dewi (Department of Mathematics Education Program IPI Garut, 2025)
Teknologi Augmented Reality (AR) kini menjadi tren yang berkembang di bidang pendidikan. Augmented Reality mempunyai kemampuan untuk menggabungkan dunia digital dan dunia nyata yang kemudian mengarah pada munculnya kemungkinan-kemungkinan baru dalam meningkatkan kualitas kegiatan belajar mengajar. Studi ini bertujuan untuk memahami seberapa efektif penggunaan Augmented Reality sebagai media alternatif dalam pembelajaran matematika di lembaga pendidikan. Studi ini menerapkan metode Systematic Literature Review (SLR) dengan mengumpulkan artikel-artikel dari berbagai jurnal internasional maupun nasional menggunakan kata kunci yang sudah ditetapkan. Terdapat 231 artikel yang ditemukan pada tahap awal pencarian dengan total 23 artikel yang memenuhi kriteria inklusi dan eksklusi. Hasilnya pemanfaatan AR dalam pendidikan matematika telah diterapkan dan diterapkan sebagai media pendukung pembelajaran interaktif di berbagai tingkatan mulai dari sekolah dasar hingga perguruan tinggi. Temuan dari ulasan ini mendukung literatur mengenai pemanfaatan Augmented Reality sebagai media alternatif dalam pembelajaran matematika. Augmented Reality (AR) technology has become an emerging trend in the field of education. AR is capable of integrating digital elements with the real environment, thereby creating new opportunities to enhance the quality of teaching and learning processes. This study aims to understand how effective the use of Augmented Reality as an alternative media in mathematics learning in educational institutions is. This study applies the Systematic Literature Review (SLR) method by collecting articles from various international and national journals using predetermined keywords. There were 231 articles found in the initial stage of the search with a total of 23 articles meeting the inclusion and exclusion criteria. The results show that AR has been applied and implemented in mathematics education as a supporting media for interactive learning at various levels, from elementary school to university. The findings of this review support the literature on the use of Augmented Reality as an alternative medium in mathematics learning.